Electrospray ionization multi‐stage mass spectrometric study of the interaction products of the cytotoxic complex [Cu(thp)4][PF6] with methionine‐rich model peptides. (28th December 2014) - Peruzzo, Valentina; Tisato, Francesco; Porchia, Marina; Santini, Carlo; Pellei, Maura; Traldi, Piero
<x xml:space="preserve">Abstract</x> RATIONALE The cytotoxic activity of the copper(I) complex [Cu(thp)4][PF6] (CP) (thp = tris(hydroxymethyl) phosphine) is correlated with its high accumulation in cancer cells. Human copper transporter 1 (hCtr1) has been described as the main trans‐membrane protein involved in cellular trafficking of physiological copper. Methionine‐rich peptide sequences incorporated in the extracellular domain of hCtr1 play a key role in the cellular internalization of copper. We wish to investigate the interaction of CP with model peptides that mimic the extracellular domain of hCtr1. METHODS The interaction of CP with methionine‐rich and methionine‐free model peptides has been investigated by electrospray ionization mass spectrometry and the interaction products have been characterized by multiple collisional experiments, using an ion trap mass instrument. RESULTS The interaction of CP with selected methionine‐rich model peptides, Ac‐MMMMPMTFK‐NH2 (P1) and Ac‐MGMSYMDSK‐NH2 (P2), shows that the native copper complex, after sequential loss of phosphines, induces the formation of [Cu(P1)(thp)]+ and [Cu(P1/P2)]+ adducts reasonably by inclusion of the Cu(I) ion in the peptide framework. Collisionally induced fragmentations (MSn) of [Cu(P1/P2)]+ give evidence that the metal is coordinated by the thioether‐S of two adjacent methionine residues. Interaction of the same peptides with the isostructural complex [Ag(thp)4]+ or AgNO3 yields similar experimental evidence, leading to [Ag(P1/P2)]+. CONCLUSIONS Methionine sequences incorporated in model peptides are crucial for the recruitment of copper from CP. Such a metal‐peptide interaction does not take place when methionine‐free Ac‐NleGNleSYNleDSK‐NH2 (P3) is utilized. A mechanism for tumor cell internalization of CP involving: (i) chemically driven sequential loss of phosphines from the native tetrahedral complex, followed by (ii) transfer of Cu(I) to the methionine‐rich sequences typical of the hCtr1 transporter, is proposed. Copyright © 2014 John Wiley & Sons, Ltd.